2019
DOI: 10.1074/jbc.ac119.007558
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte–macrophage colony-stimulating factor inactivation in CAR T-cells prevents monocyte-dependent release of key cytokine release syndrome mediators

Abstract: Edited by Peter Cresswell Chimeric antigen receptor T-cell (CAR T-cell) therapy has been shown to be clinically effective for managing a variety of hematological cancers. However, CAR T-cell therapy is associated with multiple adverse effects, including neurotoxicity and cytokine release syndrome (CRS). CRS arises from massive cytokine secretion and can be life-threatening, but it is typically managed with an anti-IL-6Ra mAb or glucocorticoid administration. However, these treatments add to a patient's medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
138
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(146 citation statements)
references
References 37 publications
2
138
0
6
Order By: Relevance
“…10,[30][31][32] These cytokines have also been implicated in a number of other CNS diseases 33 and are known to activate the endothelial cells at the BBB, 9,34,35 supporting the theory that ICANS is initiated by a systemic cytokine surge. Key inflammatory cytokines showed similar elevations in the CSF and serum, suggesting that local cytokine production in the CNS is not a prominent feature of neurotoxicity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…10,[30][31][32] These cytokines have also been implicated in a number of other CNS diseases 33 and are known to activate the endothelial cells at the BBB, 9,34,35 supporting the theory that ICANS is initiated by a systemic cytokine surge. Key inflammatory cytokines showed similar elevations in the CSF and serum, suggesting that local cytokine production in the CNS is not a prominent feature of neurotoxicity.…”
Section: Discussionmentioning
confidence: 81%
“…Evidence is emerging that T cells may activate monocytes through granulocyte macrophage colony-stimulating factor and that the monocytes are an important source of proinflammatory cytokines. 10,[30][31][32] These cytokines have also been implicated in a number of other CNS diseases 33 and are known to activate the endothelial cells at the BBB, 9,34,35 supporting the theory that ICANS is initiated by a systemic cytokine surge.…”
Section: Discussionmentioning
confidence: 81%
“…CRS is dose-limiting and often necessitates additional interventions, with the IL-6 blocking antibody tocilizumab currently the front-line treatment (Maude et al, 2014) . Pre-clinical studies have also shown that disarming GM-CSF alone using CRISPR inactivation in CAR-T cells or administering blocking antibodies significantly reduces CRS-like symptoms in vitro and in patient-derived xenograft models (Sachdeva et al, 2019;Sterner et al, 2019) . Importantly, two recent phase-I clinical trials (Brudno et al, 2020;Ying et al, 2019) have shown that broadly attenuated CAR-T cell cytokine release can lead to reduced incidence of high-grade CRS and neurotoxicity without compromising the anti-tumour potency of CD19-directed CAR-T cell therapy in B-cell lymphoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…http://jitc.bmj.com/ Open access cells dramatically lowers IL-6 and IL-8 secretion 102 and therapeutic inhibition of GM-CSF reduces CAR T-cellassociated CRS in mouse models. 103 Initial evidence from a study of 52 patients with COVID-19 reported from Wuhan, China, elevated levels of circulating GM-CSF were associated with worse clinical outcomes.…”
Section: Interferon Gammamentioning
confidence: 99%